Essential Oil Composition and DPPH Scavenging Activity of Endemic Tanacetum mucroniferum Hub. - Mor. & Grierson from Turkey - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2012)
Water-distilled essential oil from flowers of Tanacetum mucroniferum from Turkey were analyzed by GC and GC-MS. The flower oil of T. mucroniferum was characterized with oxygenated monoterpenes and oxygenated sesquiterpenes. Main components of the oil were 1,8-cineole 21.9 % and camphor 6.4 %. Antioxidant activity of the oil was determined at various concentrations and incubation time by DPPH radical protocol. Highest activity was observed at 20 mg/mL concentration (22.31 %) with 60 minutes incubation time. When compared with positive control a-tocopherol (96.59 %) at same conditions oil showed low DPPH scavenging activity. T. mucroniferum was reported to be an intermediate species between T. sipikorense and T. aucheranum. Essential oil composition of T. mucroniferum was investigated for the first time and similarities with previously reported T. aucheranum essential oil was compared.
Keywords: Tanacetum mucroniferum; Asteraceae; essential oil; 1,8-Cineole; Camphor; DPPH radical scavenging activity; SCHULTZ BIP.; VULGARE L.; ANTIMICROBIAL ACTIVITY; ENANTIOMERIC DISTRIBUTION; ANTIBACTERIAL ACTIVITY; CHEMICAL-COMPOSITION; VAR. ARGYROPHYLLUM; GROWING WILD; BALSAMITA L.; HEYWOOD